A feasibility study to determine the benefits of upper extremity virtual rehabilitation therapy for coping with chronic pain post-cancer surgery. Issue 4 (November 2016) - House, Gregory; Burdea, Grigore; Grampurohit, Namrata; Polistico, Kevin; Roll, Doru; Damiani, Frank; Hundal, Jasdeep; Demesmin, Didier
Background: Persistent pain in shoulder and arm following post-surgical breast cancer treatment can lead to cognitive and physical deficits. Depression is also common in breast cancer survivors. Virtual reality therapy with integrative cognitive and physical rehabilitation has not been clinically trialed for this population. The novel BrightArm Duo technology improved cognition and upper extremity (UE) function for other diagnoses and has great potential to benefit individuals coping with post-surgical breast cancer pain. Objectives: The aim of this study was to explore the feasibility of BrightArm Duo therapy for coping with post-surgical chronic pain and associated disability in breast cancer survivors with depression. Methods: BrightArm Duo is a robotic rehabilitation table modulating gravity loading on supported forearms. It tracks arm position and grasping strength while patients play three-dimensional (3D) custom integrative rehabilitation games. Community-dwelling women (N = 6) with post-surgical breast cancer pain in the upper arm trained on the system twice a week for 8 weeks. Training difficulty increased progressively in game complexity, table tilt and session length (20–50 minutes). Standardized assessments were performed before and after therapy for pain, cognition, emotion, UE function and activities of daily living. Results: Subjects averaged upwards of 1300 arm repetitions and 850 hand grasps per session. Pain intensity showed a 20% downward trend (p = 0.1) that was corroborated by therapist observations and participant feedback. A total of 10 out of 11 cognitive metrics improved post-training (p = 0.01) with a significant 8.3-point reduction in depression severity (p = 0.04). A total of 17 of 18 range of motion metrics increased (p < 0.01), with five affected-side shoulder improvements above the Minimal Clinically Important Difference (8°). In all, 13 out of 15 strength and function metrics improved (p = 0.02) with lateral deltoid strength increasing 7.4 N on the affected side (p = 0.05). Conclusion: This pilot study demonstrated feasibility of using the BrightArm Duo Rehabilitation System to treat cancer survivors coping with upper body chronic pain. Outcomes indicate improvement in cognition, shoulder range, strength, function and depression.